Development and improvement of the car seat polyurethane injection moulding process / Ahmed Jaffar and Jamaluddin Mahmud. - Jaffar, Ahmed; Mahmud, Jamaluddin (2006)
The development and improvement of the automotive seat is attracting increased attention from vehicle manufacturers. It is recognized that seat styling, comfort and its ergonomic functions as well as safety contribute to the initial appeal of a vehicle towards its customer; in other words meeting customer satisfaction. The durability of the car seat can be reflected in the vehicle's residual value. Car seat polyurethane injection (p/u) moulding process is a method of producing car seat in an attempt to meet the said objectives. This project has explored the application of an industrial robotics and the development of flexible line automation for car seat polyurethane injection molding process using work study method and Delmia Quest Simulation Software (DQSS). Financial analysis was then carried out in determining the Payback Period to justify the actual investment cost before it is materialized. Comparisons between proposed methods against the existing method was done to identify the improvements in terms of productivity and product quality and eventually cost effectiveness achieved; through layout improvements, line automation and robotics applications.